#### Answer

$6(x-5)(x+2)$

#### Work Step by Step

Factor out the GCF of $6$ to obtain:
$=6(x^2-3x-10)$
The leading coefficient of the trinomial is 1.
Factor the trinomial by looking for factors of the constant term $(-10)$ whose sum is equal to the coefficient of the middle term $(-3)$.
Note that $-10=-5(2)$ and $-5+2=-3$.
This means that the factors we are looking for are $-5$ and $2$, and that the factored form of the trinomial is $(x-5)(x+2)$.
Thus, the completely factored form of the given polynomial is:
$=6(x-5)(x+2)$